Adapting Problem Tree-Assisted Small-Group Facilitation to Strengthen Collaborative Decision-Making Foundations in Early Childhood Education: Insights from Elementary Classroom Action Research - Raodhatul Jannah M (Lia Center of Research and Education, 2025)
This study investigates challenges in Civic Education, particularly the development of deliberation skills among fifth-grade students at Yaminas Islamic Elementary School, Noling. Observations revealed ten students struggled to regulate emotions during discussions, often rejecting differing opinions with negative expressions or arguments. Classroom participation was also dominated by a few voices, limiting collaboration and equity. To address these issues, a Classroom Action Research (CAR) design was applied, combining small-group facilitation with the “problem tree” method. The intervention proceeded in two cycles: planning, implementation, observation, and reflection. In Cycle I, the theme was “Flood Issues and Solutions,” identifying waste as the root problem. In Cycle II, the focus shifted to “Effective Waste Management,” with flooding as the key concern. Deliberations were organized through small-group, large-group, and plenary sessions to balance participation. Findings showed clear improvement. The average score increased from 23 in Cycle I to 32 in Cycle II, indicating progress in participation, emotional regulation, and consensus-building. Although situated in an elementary school, the results offer insights for Early Childhood Education (ECE). Structured facilitation and problem tree media can be adapted for play-based contexts, helping young children practice turn-taking, negotiation, perspective-taking, and collective decision-making. These foundations strengthen social-emotional skills and prepare children for civic readiness from early ages.